Home sweet home: The home bias in trade in the European Union - Alina Mika (European Central Bank (ECB), 2017)
This study examines the home bias in trade in goods and services within the European Union. Using the newest release of the World Input Output database, available for the years 2000-2014, the effect is estimated using gravity regressions. The trade-reducing effect of borders is found to be sizeable. It is greater for trade in services than for goods, though the former declined more markedly throughout the period. The paper extends current literature by demonstrating and analysing the variation in the bias across Europe. The border effect is larger in Central and Eastern Europe than in other parts of the continent. The differences in the effect can be largely explained by the depth of a country's integration with the European Union. The number of years passed since a country joined the EU has a significant impact on the bias. The longer a country has been in the EU, the lower its home bias, with the first years of membership having the largest (in absolute terms) effect.
Keywords: F02; F15; F14; 330; trade; gravity; border effect; European Union